Do Politicians Shirk when Reelection Is Certain? Evidence from the German Parliament - Andreas Bernecker (University of Mannheim, Department of Economics, 2013)
Does stiffer electoral competition reduce political rent-seeking behavior? For a microanalysis of this question, I construct a new data set spanning the years 2005 to 2012 covering biographical and political information of German members of parliament (MPs) and including attendance rates in voting sessions for the first time. For the parliament elected in 2009, I show that indeed MPs who expect to face a close race in their district show significantly and relevantly lower absence rates in parliament beforehand. MPs of governing parties seem to react less to electoral competition. These results are confirmed by an analysis of the parliament elected in 2005, by several robustness checks, and also by employing an instrumental variable strategy exploiting convenient peculiarities of the German electoral system. This study is also the first to analyze how MPs elected via party lists react to different levels of electoral competition.
urn:nbn:de:bsz:180-madoc-333729
Keywords: D72; H11; J45; 330; Accountability; Political Competition; Quality of Politicians; Rent-Seeking; Absences